Urgensi Sejarah Sosial Sebagai Konsep Teoretis Bagi Living Hadith di Indonesia - Dewi, Subkhani Kusuma (Religió: Jurnal Studi Agama-agama, 2018)
The perspective on Islamic history has become an important topic of discussion in Islamic studies. Its existence, at the same time, is also very helpful in the study of texts, such as the interpretation of the Alqur'an or riwâyat and dirâyat studies of Hadith. But the existence of social history as a new theoretical concept came later. A perspective that emphasizes on the sociological aspects of a collection of events, social history also puts forward the process of criticism in it, as has been done by peripheral social history. In the first sub-chapter, this article needs to show that such a perspective has long been carried out by Muslim historians, such as Ibn Khaldun, or Hamzah Al-Sam'ani's Tarikh Jurjan. Unlike the political perspective, the history of Muslim societies have varieties of fragments, different kinds of local tradition and focus on social history. The second part of this article proves that the existence of ijâzah (authorization) as a juristic authority through the tradition of sanad is another way of the documentation for the transmission (or also transformation) of Hadith in the community. Hadith authority does not take place statically. Social history narratives in this context will be able to provide evidence that authority of Hadith local religious leaders would not be possible if there were no community acceptance as explored by its various dimensions (economic, social, political, religious) through social history. [Cara pandang terhadap sejarah islam telah menjadi topik diskusi penting dalam studi Islam. Keberadaannya, pada saat yang sama, juga amat membantu studi teks, seperti tafsir Qur’an ataupun studi riwâyat dan dirâyat Hadith. Tetapi keberadaan sejarah sosial sebagai sebuah konsep teoritik baru datang belakangan. Sebuah cara pandang yang menekankan pada aspek sosiologis sebuah kumpulan peristiwa, sejarah sosial juga mengedepankan proses kritisisme di dalamnya, seperti yang telah dilakukan oleh sejarah sosial pingiran. Pada sub-bab pertama, artikel ini berkebutuhan untuk menunjukkan bahwa cara pandang seperti ini telah lama dilakukan oleh sejarawan muslim, seperti Ibn Khaldun, ataupun Tarikh Jurjan karya Hamzah Al Sam’ani. Berbeda dengan perspektif politik, sejarah masyarakat muslim adalah ragam fragmen, ragam sejarah lokal yang berbeda-beda, focus pada sejarah sosial. Bagian kedua dari artikel ini membuktikan bahwa keberadaan ijâzah (otorisasi) sebagai penyambung otoritas keulamaan melalui tradisi sanad merupakan bahasa lain dari dokumentasi transmisi (atau juga transformasi) Hadith di masyarakat. Otoritas Hadith tidak berlangsung secara statis. Narasi sejarah sosial pada konteks ini akan mampu menyuguhkan bukti bahwa suatu otoritas atau kewenangan Hadith para local religious leaders tidak akan mungkin diakui bila tidak ada penerimaan masyarakat sebagaimana diekplorasi ragam dimensinya (ekonomi, sosial, politik, agama) melalui sejarah sosial.]